Model for Providing Wrap-Around Care for Patients with Substance Use Disorders at a Single-Site, Urban Student-Run Free Clinic - Terence Hughes; Bhavana Patil; Elizabeth Magill; Jeremy Sherman; Arianna N Davis; Benjamin Shuham; Kevin Weiss; Paloma Orozco Scott; Maria Meyer; Craig Katz; Yasmin Meah (Journal of Student-Run Clinics, 2025)
Patients with substance use disorders (SUDs) have low levels of care access and utilization, driven by factors such as medical provider stigma, disinterest and inadequate education. Student-run free-clinics (SRFCs) are uniquely positioned to begin addressing these interlocking problems, with impact possible both in the near and long-term - for example, the potential to increase access to care for patients with SUDs now while also preparing medical students to enter the workforce as physicians equipped to provide this population with stigma-free, evidence-based care in the future. However, few SRFC-based interventions aimed at caring for this patient population have been implemented or published in the literature. The authors aim to fill this gap by describing a pilot intervention that aspires to provide wrap-around services to patients with SUDs at the East Harlem Health Outreach Partnership (EHHOP), a single-site, urban SRFC. Prior to this intervention, EHHOP already had a strong groundwork in place to care for patients with SUDs, consisting of primary care integrated with opt-in mental health care, capable of providing both pharmacotherapy and psychotherapy. The pilot intervention described here aims to fill gaps in this groundwork, specifically (1) improved patient identification through universal patient screening and connection to immediate care through creation of a consult/liaison service, (2) increased student-provider education to address variable levels of prior experience, and (3) strengthened harm reduction infrastructure to offer both on-site education and resources, with seamless referrals to community organizations for services physically unavailable in the clinic. In describing this process of addressing gaps in effort to provide wrap-around services for EHHOP patients with SUDs, the authors aim to provide a scalable model for peer SRFCs to adapt to better their care for this patient population.